Pemaknaan Al-Mutaṭahharûn dalam al-Qur'an Dan Implikasinya Terhadap Problematika Hukum Perempuan Haid - Nur Sa'ada Mukmin; sohrah; Rosmini (LPPM IAIN Sorong, 2026)
Padang City, despite being known as a religious region that upholds Minangkabau customs and traditions rich in moral values, still faces significant challenges in implementing religious moderation. One prominent issue is the rise in intolerance and discrimination, particularly against minority groups, both socially and administratively. Eliminating this discrimination and intolerance is the ultimate goal of the Pelita Padang community, which continues to strive to implement religious moderation in the city. This paper aims to analyze the implementation of religious moderation by the Pelita Padang community in Padang City. This research uses a descriptive qualitative method with a case study approach as the basis for its analysis. Data collection uses interviews, observations, and literature. The collected data are then analyzed thematically. The findings of this study reveal that the Pelita Padang community actively contributes to implementing religious moderation in Padang City through various activities, such as interfaith dialogue, religious moderation training, socio-religious activities, and advocacy related to diversity issues. This initiative has had a positive impact in increasing awareness of the importance of tolerance and strengthening national identity among the people of Padang City